Evaluasi Program Kerja Tahunan Kepala Madrasah dalam Meningkatkan Kualitas Kinerja Guru di MTsN 2 Bengkulu Selatan - Kristanti Olivia; Retno Ambar Wati (Al-Khair Journal: Management Education, 2026)
Abstract: The purpose of this paper is to evaluate the annual work program of the madrasah principal in improving the quality of teacher performance at Madrasah Tsanawiyah Negeri 2 Bengkulu Selatan. Using a descriptive qualitative method, with the CIPP model approach (context, input, process, product). The results of the study indicate that the context of the annual work program of the madrasah principal has a program, details of needs, program objectives to improve teacher performance in madrasah. The input of the program is the existence of a madrasah principal who is able to prepare an annual work program with a budget plan, born in its derivative policies. The process of the annual work program. After the madrasah principal prepares the program, all components of the madrasah work together and continuously in realizing the common goals that have been prepared together. The product of the annual performance program of the madrasah principal, all components of the madrasah, especially educators and education personnel are able to respond and implement the program well and continuously, although there are several obstacles in the implementation of the program, such as low motivation and knowledge of teachers, teacher professional development is not optimal. Thus it can be concluded that the annual work program of the madrasah principal can improve teacher performance. Therefore, to improve teacher performance, increase the evaluation of the annual work program of the madrasah principal in the madrasah. Keywords: Evaluation, Annual Work Program of Madrasah Principal, Quality of Teacher Performance.Abstrak: Tujuan tulisan ini untuk mengevaluasi program kerja tahunan kepala madrasah dalam meningkatkan kualitas kinerja guru di Madrasah Tsanawiyah Negeri 2 Bengkulu Selatan. Menggunakan metode kualitatif deskriptif, dengan pendekatan model CIPP (context, input, process, produc). Hasil penelitian menunjukkan bahwa contex program kera tahunan kepala madrasah telah ada program, rincian kebutuhan, tujuan program untuk meningkatkan kinerja guru di madrasah. Input program adanya kepala madrasah yang mampu menyusun program kerja tahunan dengan rencana anggarannya, dilhirkan dalam kebijakan kebijakan turunannya. Proses program kerja tahunan. Setelah kepala madrasah menyusun program, maka seluruh komponen madrasah melakukan secara bersama dan berkelanjutan dalam mewujudkan tujuan bersama yang telah disusun besama-sama. Produk program kinerja tahunan kepala madrasah seluruh komponen madrasah khususnya pendidik dan tenaga kependidikan mampu merespon dan melaksanakan program tersebut secara baik dan berkelanjutan, walaupun terdapat beberapa hambatan dalam pelaksanaan program, seperti rendahnya motivasi dan pengetahuan guru, perkembangan profesional guru belum optimal. Dengan demikian dapat disimpulkan bahwa program kerja tahunan kepala madrasah dapat meningkatkan kinerja guru. Oleh karena itu, untuk meningkatkan kinerja guru, maka tingkatkanlah evaluasi program kerja tahuan kepala madrasah di madrasah. Kata kunci: Evaluasi, Program Kerja Tahunan Kepala Madrasah, Kualitas Kinerja Guru.